Clouds in brown dwarfs and giant planets. Issue 1 (6th February 2013) - Metchev, S.; Apai, D.; Radigan, J.; Artigau, É.; Heinze, A.; Helling, C.; Homeier, D.; Littlefair, S.; Morley, C.; Skemer, A.; Stark, C.
Abstract A growing body of observational and theoretical evidence points toward the importance of clouds in the atmospheres of ultra‐cool brown dwarfs and giant planets. Empirically, the presence of clouds is inferred from the red, likely dusty atmospheres of young substellar objects, and from detections of periodic variability in a fraction of brown dwarfs – as expected from rotation and a patchy cloud cover. Theoretical models have progressed alongside by including ever more comprehensive atomic and molecular opacity tables, incorporating the treatment of non‐equilibrium chemistry and clouds through vertical mixing and grain size/sedimentation parameters, and employing 3‐D hydrodynamical simulations. In this proceeding we summarize the key issues raised during the first gathering of observers and theorists to discuss clouds and atmospheric circulation in non‐irradiated ultra‐cool dwarfs and giant planets. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)